Herbal Medications to Manage Insomnia: An Overview of Clinical Trials using Herbal Treatment for Insomnia - Maryam Ranjbar; Mohammad Mazaheri; Mohammad Ansaripour; Mahmoud Babaeian; Atefeh Jalali; Mohammad Mehdi Zarshenas (Tehran University of Medical Sciences, 2022)
Insomnia is one of the most prevalent sleep disorders worldwide which significantly affects the quality of life. Pharmacological and non-pharmacological approaches have been applied in managing insomnia. The risk of tolerance and dependence on conventional medications and their other side effects leads the surveys to complementary and alternative medicine. This overview aimed to compile the clinical trials on herbal remedies in managing insomnia for facilitating future studies on medicinal plant in this issue. The keywords "Medicinal plant", "Herbal medicine" in combination with "Hypnotic and sedative", "Insomnia" or "Sleep" were searched through PubMed, Google Scholar, and Scopus electronic databases from 1st January 2000 to 31st August 2020. Then, all clinical trials focusing on the efficacy of medicinal plants on insomnia were collected. Based on the inclusion and exclusion criteria, 36 articles were selected, included 16 medicinal plants (23 studies) as a single herb and 13 polyherbal formulations. The most prevalent route of administration among these trials was oral. Matricaria chamomilla L., Valeriana officinalis L., Viola odorata L., and Passiflora incarnata L. were among the most prevalent effective herbal medicines on insomnia. Also, the modulation of the GABAergic system was the most common target of these medicinal plants. Herbal remedies can be introduced as safe and effective alternatives for conventional medications in managing insomnia. The popular herbal medicines, such as M. chamomilla, V.  officinalis, V. odorata, are suitable for further therapeutic development. Other cited medicinal plants in this review can be more investigated in improvement of sleep.